2016
DOI: 10.1109/tcsvt.2015.2504732
|View full text |Cite
|
Sign up to set email alerts
|

Improving QoE and Fairness in HTTP Adaptive Streaming Over LTE Network

Abstract: HTTP adaptive streaming (HAS) has emerged as the main technology for video streaming applications. Multiple HAS video clients sharing the same wireless channel may experience different video qualities, as well as, different play-out buffer levels, as a result of both different video content complexities and different channel conditions. This causes unfairness in the end-user quality of experience (QoE). In this paper, we propose a quality-fair adaptive streaming solution with fair buffer (QFAS-FB) to deliver f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 41 publications
(65 reference statements)
0
20
0
Order By: Relevance
“…MANE, proposed in [19], achieves fair playout buffer levels among HAS clients competing for same wireless resources by allocating radio resources according to video content characteristics, playout buffer levels and channel conditions. However, as in SAP, MANE also does not provide a means to control number of quality switches in adaptive video streams.…”
Section: B Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…MANE, proposed in [19], achieves fair playout buffer levels among HAS clients competing for same wireless resources by allocating radio resources according to video content characteristics, playout buffer levels and channel conditions. However, as in SAP, MANE also does not provide a means to control number of quality switches in adaptive video streams.…”
Section: B Related Workmentioning
confidence: 99%
“…However, as in SAP, MANE also does not provide a means to control number of quality switches in adaptive video streams. The system architecture proposed in [19] requires MANE to be located close to eNodeBs (eNBs), and requires Channel State Information (CSI) updates from eNBs. Based on these updates, it sets up rate values, i.e., Guaranteed bitrate (GBRs), that eNBs will try to guarantee to their associated clients.…”
Section: B Related Workmentioning
confidence: 99%
“…The solutions proposed in [28] and [29] employed an adaptive streaming solution to obtain high QoE for users in a fair manner based on the network conditions. However, most of them do not consider either user QoE or the energy consumption of mobile devices in the wireless environment.…”
Section: Fairness Issuesmentioning
confidence: 99%
“…In [53] and [54], the authors have identified three main performance issues: (i) player instability, (ii) unfairness between the players and (iii) the under-utilization of the available bandwidth. It is pointed out that the main cause of these [31], [32], [34], [59] × × × × × [37], [35] ×…”
Section: B Client-side Approachesmentioning
confidence: 99%